The determinants of housing price factors in Malaysia / Noor Nadzhira Hanim Yacob - Yacob, Noor Nadzhira Hanim (Faculty of Business Management, 2014)
House can be define as a place that provide a shelter or accommodation and a building in which people meet for a particular activity. Malaysia as a developing country has obtained benefits from the development of housing industry. Over the past few years, housing price in Malaysia experienced significant price expansion with higher rates throughout Malaysia. Therefore, sudden price change could affect home ownership to some extent. Under any circumstances, the need for housing is a basic necessity persists. The objective is to determine the relationship between prices movements households income, stock price, cost of construction, population change, Gross Domestic Product (GDP), and interest rates. This study is using quarterly time series data from January 2005 until December 2013. The multiple linear regressions were used in this study to analyse the relationship between independent variable (population change, Gross Domestic Product (GDP), households’ income and interest rates) towards dependent variable (affordability in purchasing housing in Malaysia). The expect findings suggest that the movement of housing price in Malaysia is determined by changes in population change, Gross Domestic Product (GDP), households’ income and interest rates.